Animated Powtoon-Based Video to Improve the Ability to Understand Sound Science - Solehah, Nur Faridatus; Setiawan, Deni (Jurnal Penelitian Pendidikan IPA, 2023)
Sound is one of the most critical components of singing. A lack of sound understanding can affect students' ability to sing due to the lack of use of learning media in class. The study aimed to determine the effectiveness and feasibility of Powtoon-based animated video learning media on singing abilities in third-grade students using the 10-step Research and Development (R&D) research method developed by Borg and Gall. Data collection techniques using observation, interviews, questionnaires, and documentation. The results of product data analysis in the form of learning media validation were carried out by experts in the field of materials and media with a percentage of 83.75% and 87.5% with the criteria of "very feasible." The effectiveness of the developed media is known based on the increase in the percentage of students' pretest and posttest scores on the knowledge aspect of 0.43% in the "moderate" category and 0.31% in the skills aspect in the "moderate" category. The results of the teacher and student response questionnaire to the media obtained a percentage of 79.57% with the "very decent" criteria. Based on this, portion-based animated videos can improve students' sound understanding and ability to sing and are suitable for use as a support for the learning process in elementary schools.